2020
DOI: 10.1016/j.jcp.2020.109369
|View full text |Cite|
|
Sign up to set email alerts
|

A new and consistent well model for one-phase flow in anisotropic porous media using a distributed source model

Abstract: A new well model for one-phase flow in anisotropic porous media is introduced, where the mass exchange between well and a porous medium is modeled by spatially distributed source terms over a small neighborhood region. To this end, we first present a compact derivation of the exact analytical solution for an arbitrarily oriented, infinite well cylinder in an infinite porous medium with anisotropic permeability tensor in R 3 , for constant well pressure and a given injection rate, using a conformal map. The ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…When these are placed close together in the same FV cell, we find ourselves in Case 2.1 , and Assumption 2 in Section 2.6 breaks down. In this case, models that don’t integrate an analytical description of interactions among sources [ 37 , 72 ] fail to capture the source to sink interactions. With increasing separation distance d between the source and sink, Assumption 2 is recovered but, depending on the size of , the deviation from Assumption 1 may increase ( Case 1.3 ).…”
Section: Results: Error Estimationmentioning
confidence: 99%
“…When these are placed close together in the same FV cell, we find ourselves in Case 2.1 , and Assumption 2 in Section 2.6 breaks down. In this case, models that don’t integrate an analytical description of interactions among sources [ 37 , 72 ] fail to capture the source to sink interactions. With increasing separation distance d between the source and sink, Assumption 2 is recovered but, depending on the size of , the deviation from Assumption 1 may increase ( Case 1.3 ).…”
Section: Results: Error Estimationmentioning
confidence: 99%
“…We have shown that the reconstruction significantly reduces the discretization error. Another approach is the Peaceman well model known in reservoir engineering [27,36,37]. Peaceman devises a reconstruction method eliminating discretization errors for one specific discretization scheme, and with some assumptions on the structure of the mesh and the orientation of the well tube.…”
Section: Summary and Final Remarksmentioning
confidence: 99%
“…Introducing the Joukowski function , defines the transform as follows where z = x + i y and w = u + i v = M e iθ , and based on Euler formula, we can get …”
Section: Mathematical Model Of Multiregion Coupling Flowmentioning
confidence: 99%
“…43,44 An analytic function is introduced which transforms from the elliptic domain to circular domain (Figure 5), and the original problem is solved by using the inverse transformation. Introducing the Joukowski function 45,46 defines the transform as follows…”
Section: Mathematical Model Of Multiregionmentioning
confidence: 99%